Urban bird communities and conservation status in Pekanbaru, Riau, Indonesia - HADINOTO HADINOTO; ENI SUHESTI; EDDISYAH PUTRA PANE (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hadinoto, Suhesti E, Pane EP. 2025. Urban bird communities and conservation status in Pekanbaru, Riau, Indonesia. Biodiversitas 26: 6099-6110. Urban green spaces can sustain considerable avian diversity in rapidly expanding tropical cities, yet empirical evidence from Indonesia remains limited. We assessed species composition, conservation status, and functional guilds across a mosaic of green open spaces in Pekanbaru, Riau Province, Indonesia. Using standardized point counts and transect surveys, we recorded 71 species from 35 families, including three migratory taxa. Thirteen species are nationally protected; 16 appear on the IUCN Red List (CR-NT); and six occur in the CITES Appendices, notably Appendix I Leucopsar rothschildi. Functional composition was dominated by insectivores, indicating potential contributions to urban pest regulation. Habitat associations and feeding guilds mediated vulnerability: wetland and insectivore dependent species were most sensitive to habitat degradation, whereas granivores were affected by agricultural land use change. The co-occurrence of nationally protected and globally threatened taxa within urban green spaces underscores their dual role as refugia and actionable conservation targets within the urban matrix. Nevertheless, persistent pressures habitat loss, land use conversion, and illegal wildlife trade threaten population persistence and complicate management. We recommend integrating multi-scale urban green-space planning with active population monitoring, stronger enforcement against wildlife trade, and targeted habitat management focused on wetland elements and insect resources. These measures can help maintain avian diversity and sustain ecosystem services provided by birds in tropical cities, while offering practical entry points for city level biodiversity strategies.